Examining the 2013 Kansas state income tax changes and their impact on job creation - Blagg, Brandon (Kansas State University, 2015)
I analyze the impact of Kansas House Bills HB 2117 and HB 2059, which made changes to the personal income tax structure and sales tax rates in the state of Kansas in 2012 and beyond. Using county-level, quarterly data gathered from the Census Bureau and the Bureau of Economic Analysis, I examine a full sample of Kansas and its four bordering states; Colorado, Missouri, Nebraska, and Oklahoma in order to determine the impact the tax changes had on the private sector employment in the state of Kansas. I subsequently use Kansas county-level, quarterly data to create a sample of Kansas border counties and their border pair matches, which consist of their adjacent counties in the neighboring states, to employ a differencing model to examine those same effects. With this analysis I isolate the policy change taking place in Kansas in 2012 and assess its impact controlling for the impact of the state corporate income tax, individual income tax, and sales tax rates on private sector employment in Kansas counties. My findings indicate that Kansas has not experienced an increase in private sector employment due to this policy change, but rather has perhaps seen private sector employment levels fall in the year following the enactment of the policy change.
Keywords: Tax; Kansas; Employment; Brownback; Income tax; Economics (0501); Public Policy and Social Welfare (0630)